2011
DOI: 10.1039/c1nr10194c
|View full text |Cite
|
Sign up to set email alerts
|

Field nanoemitter: One-dimension Al4C3 ceramics

Abstract: As a kind of ionic (or salt-like) carbide, Al(4)C(3) hardly any active functions have been found except for structure material purposes. However, considering the unique characteristic features of its crystal structure, we think Al(4)C(3) in fact might have huge potential for exhibiting active functionality on field-emission application. Herein, we report for the first time the catalyst-free synthesis and excellent field emission properties of Al(4)C(3) one-dimension (1-D) nanostructures. The 1-D nanostructures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…The observation of G-and D-band peaks is strong evidence that the structure of the CNT is retained. Typical active Raman peaks for Al 4 C 3 were observed at 255, 337, 494, and 868 cm À1 [19]. A peak from Al 4 C 3 (868 cm À1 ) was observed in the dispersed CNT curve (red curve), again supporting the argument for the formation of Al 4 C 3 at the boundary between Al and the CNTs.…”
Section: Resultssupporting
confidence: 51%
“…The observation of G-and D-band peaks is strong evidence that the structure of the CNT is retained. Typical active Raman peaks for Al 4 C 3 were observed at 255, 337, 494, and 868 cm À1 [19]. A peak from Al 4 C 3 (868 cm À1 ) was observed in the dispersed CNT curve (red curve), again supporting the argument for the formation of Al 4 C 3 at the boundary between Al and the CNTs.…”
Section: Resultssupporting
confidence: 51%
“…The spectrum is comprised of six bands, which correspond closely to those reported previously. 5,6 There is no evidence of bands from carbon in the recorded spectra; bands for disordered (D) and ordered (graphitic; G) carbon would be expected at 1350 cm -1 and 1590 cm -1 for respectively. 29 Further, there are no bands for other Al-containing species such as the various polymorphs of Al2O3 30 and hence Raman spectroscopy would support diffraction evidence that the only product of the microwave reactions is Al4C3.…”
Section: Introductionmentioning
confidence: 99%
“…15 Recently the nanostructured carbide itself has been demonstrated to be a potentially useful functional material, with 1D Al4C3 nanowires acting as cold electron emitters with promising field emission performance. 5,6 With the global push to improve the green credentials of large-scale industry, a key focus of research has become the investigation of alternative synthesis and processing methods to reduce energy consumption and pollution. 16 Previous work has shown that solid state reaction times can be cut by orders of magnitude by switching from conventional heating to microwave (MW) heating processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Raman spectra of samples fabricated at 760°C depicted in Fig. 3 clearly indicate that the composites fabricated at t c = 15 and t c = 45 min show the same Raman-active modes than those previously derived for aluminum carbide from experimental measurements and numerical calculations [23].…”
Section: Resultsmentioning
confidence: 55%